KESIAPAN BADAN PERTANAHAN NASIONAL KOTA SAMARINDA DALAM PENERBITAN SERTIFIKAT 1 (SATU) LEMBAR (MENURUT PERATURAN MENTERI AGRARIA DAN TATA RUANG / KEPALA BADAN PERTANAHAN NASIONAL NOMOR 7 TAHUN 2016 TENTANG /BENTUK DAN ISI SERTIFIKAT HAK ATAS TANAH) - Muchamad Naufal Zakiy; Jaidun jaidun (Law Department, University of Widya Gama Mahakam Samarinda, 2018)
Human and land have a strong relations, very pure and undivided. It can be understood, because land is a home, provide food, birth place, buried place, and home of the ancestor. There are always a relations between human and land, society and a land. The constitution in 1945 article 33 clause 3 mention that earth, water and space with all its contents are controlled by nation and uses for public prosperity, that regulated in land laws are the gift of God almighty, based on rule right from the nation, so its become the government responsibility to perform land registration in all of territory of Republic Indonesia based on law number 5 year 1960 about basic rule of principles of agrarian that further mentioned in UUPA that individualistic, communal, religious, it aims to protect the land and manage the relation of land right through the certificate submission as a proof of land right for it owner. Article 4 clause 2 mention that certificate that mentioned in clause 1 is printed in one sheet based on information from physical and juridical data also equipped by owner’s photo. As one of society essential needs, land have an important roles in society lives. In the process of achieving the certificate, land registration process must be adjusted to law and technology development and society needs that regulated in Ministerial Regulation of Agrarian and Spatial / Head of National Land Agency number 7 year 2017 about shape and content of certificate of land right.